Analisis Modeling Of Islamic Corporate Culture pada Bank Syariah dalam Meningkatkan Nilai Kinerja Perusahaan (Studi Kasus pada PT. Bank BNI Syariah Cabang Pusat dan PT. Bank Mandiri Cabang Pusat) - Hasbi Ash Shiddieqy (JURNAL KAJIAN ISLAM MODERN, 2022)
In a study entitled Analysis of Modeling of Islamic Corporate Culture in Islamic Banks in Increasing Company Performance Value (Case Study at PT. Bank BNI Syariah Central Branch and PT. Bank Mandiri Syariah Central Branch), researchers tried to see how much influence corporate culture has on performance. In this study, using a qualitative approach with the method of empirical studies, namely looking at the phenomena found in Bank Syariah Mandiri and Bank BNI Syariah and seeing the comparison based on existing theories. Islamic financial institutions are a reflection of the application of sharia in life. In supporting this application, a conducive atmosphere is needed that is supportive. In the formation of this atmosphere, something is needed, namely Corporate Culture or Corporate Culture. In implementing the corporate culture, it is hoped that it can provide beneficial feedback, namely increasing the value of the company which is reflected in the performance of the company's employees.